Characteristics of sinonasal fibrous dysplasia: experience from a single department. (2nd January 2018) - Duan, Chen; Dai, Qi; Liu, Quan; Yu, Hongmeng
Abstract: Objectives: We summarized the characteristics of fibrous dysplasia patients in our department to obtain clinical data on this disease. Methods: We retrospectively reviewed 28 patients who were diagnosed with sinonasal fibrous dysplasia based on pathological examination results from March 2012 to February 2017 in our department. Results: The 28 patients included 16 females and 12 males, and the median age was 31.5 (range, 7–69) years. The three most common symptoms were nasal obstruction (25%), impaired vision (21%) and headache (18%). Most of the tumors were located in the sphenoid sinus (50%), nasal cavity (39%) or ethmoid sinus (36%). The surgical strategy included an exclusive endoscopic approach (25 cases) and an endoscopic approach combined with sublabial incision (three cases). The median follow-up period was 29 months (range, 3–62 months), and three patients were lost to follow-up. Two of the remaining 25 patients developed recurrence. However, since the second surgery, there has been no recurrence to date. Conclusions: Our study indicates that the treatment of fibrous dysplasia patients should be tailored according to patient and disease characteristics. The main surgical procedure is the endoscopic approach, and the effect is good. Although the recurrence rate is low, follow-up is necessary.